Electro-mechanical de-icing system for a non-rotating structure of small and medium sized helicopters synthesis of a helicopter control system using inverse dynamics and its upgrade with the use of a sidestick controller - Efremov, A.V.; Efremov, E.V.; Mbikayi, Z.; Esaulov, S.Y.; Ivchin, V.A.; Myasnikov, M.I. (My University, 2020)
The modern trend of developing highly automated aircraft is characterized by a transition from traditional methods and technical solutions to innovative approaches of creating control systems, inceptors and displays. This paper deals with the development of helicopter control systems based on the inverse dynamics and its integration with a novel type of side stick shaping the pilot output signal such that it is proportional to the control force (Force Sensing Control – FSC). The synergetic asset arising from this integration is also evaluated. The evaluation of the effectiveness of the inverse dynamics was carried out through mathematical modeling of the pilot-aircraft system ground based simulations.